2019
DOI: 10.1021/acs.molpharmaceut.8b01172
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfinement Effects on the Glass Transition and Crystallization Behaviors of Nifedipine

Abstract: The impact of nanoconfinement on the crystallization and glass transition behaviors of nifedipine (NIF) has been investigated using differential scanning calorimetry. Nanoconfinement was provided by imbibing the NIF into a porous medium (controlled pore glass, CPG), and results were compared with the unconfined bulk material. Consistent with previous results from the literature, both glass transition temperature T g and melting temperature T m decrease with decreasing pore size. The melting temperature was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(99 citation statements)
references
References 89 publications
4
93
2
Order By: Relevance
“…[16][17][18][19] ). This amorphous layer was indeed observed for several systems like benzene 13 , water 19 , nifedipine 11 , acetaminophen 18 or ibuprofen 20 , to name a few.…”
Section: Please Cite This Articlementioning
confidence: 65%
See 1 more Smart Citation
“…[16][17][18][19] ). This amorphous layer was indeed observed for several systems like benzene 13 , water 19 , nifedipine 11 , acetaminophen 18 or ibuprofen 20 , to name a few.…”
Section: Please Cite This Articlementioning
confidence: 65%
“…The amorphous state can be stabilized when the pore diameter is small enough to inhibit the crystallization, i.e. the nucleation process being inhibited by spatial restriction [8][9][10][11] . The attempt to establish an empirical correlation between the diameter of the pores and the size of the molecule and its physical state or states under confinement can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Even though many studies have reported drug loading into various silica carriers under specific conditions [21,22,[26][27][28][29], the determination of the maximum drug loading amount into MPS is not clearly understood, particularly for the amorphous drugs categorized in class III, based on Taylor's classification, which has good glass formers that neither crystallize upon cooling nor reheating [15,29]. It is necessary to determine maximum drug loading experimentally to maximize its effect because drugs in MPS have shown incomplete release, although a supersaturated solution has been shown to be generated.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was reported that TV of NIF was observed even though the NIF was incorporated into controlled pore glasses (CPG) with a size of 7.5, which is similar to the size of the pores of MS, although the T g decrease. Furthermore, the T g of NIF was reduced by nanoconfinement due to an intrinsic size effect indicating that the mobility of NIF in MS was higher than amorphous NIF ( Cheng and McKenna, 2019 ). However, in this study, the T g of NIF was not observed after incorporating into MS, even in the weight ratio of 4:6.…”
Section: Resultsmentioning
confidence: 99%
“…Although NIF was categorized into class II base on Taylor's classification and the crystallization of NIF was not observed in MS. A previous study reported a crystallization of NIF within controlled pore glass at a size above 22.6nm, while no crystallization was detected at 7.5nm and 12 nm, which is similar to the pore size of MS. The nanoconfinement effect of MS inhibits the formation of the critical nucleus size and crystallization of NIF ( Ambrogi et al., 2007 ; Cheng and McKenna, 2019 ).…”
Section: Discussionmentioning
confidence: 99%